ANALYSIS OF THE INFLUENCE OF JOB SATISFACTION, TRANSFORMATIONAL LEADERSHIP, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) ON EMPLOYEE PERFORMANCE AND ITS IMPACT ON EMPLOYEE RETENTION IN MANUFACTURING COMPANIES IN INDONESIA - Riadi, Farid; Riani, Dini; Sunarsi, Denok (Jurnal Riset Bisnis dan Manajemen, 2025)
This research aims to analyze the influence of job satisfaction, transformational leadership, and Organizational Citizenship Behavior (OCB) on employee performance and their impact on employee retention in manufacturing companies in Indonesia. Job satisfaction, transformational leadership, and OCB are important variables in human resource management that can influence individual and organizational performance as a whole. This research uses quantitative methods with descriptive and explanatory approaches. Data was collected through a survey involving 300 employees from several manufacturing companies in Indonesia who were selected using purposive sampling. The research results show that the variables of job satisfaction, transformational leadership, and OCB influence employee performance, and employee performance influences employee retention, namely good performance will have an impact on reducing employee retention levels.